Interspecies liminality on the edge of life: human-animal companionship in Madame (1989) - Taşdizen, Burak (İstanbul Bilgi Üniversitesi)
[EN] This article argues for liminality as a mutual, interspecies experience as well as a constituent of human-companion animal bond. Despite its potential for animal scholarship, research on interspecies liminality remain rather scarce. Drawing upon this research gap, the main objective of this study is to explore the experiences of liminality of human and feline protagonists in Halit Refiğ’s film Madame [Hanım] (1989) through its analysis conducted in adherence with the coding principles of Grounded Theory. Experiences of liminality of the human and feline protagonists in the film are closely related to the status passages of the characters’ lives. While the film narrates human liminality between living and dying at the end of Olcay’s life, the feline character Hanım depicts liminality of the animal subject between person and property as well as spatial (non)belonging thereof due to her human companion Olcay’s dying. Findings of the study indicate that, in addition to the category of liminal animals being a descriptor for animal populations in proximity to human settlements, liminality lens could be employed to understand life trajectories of individual animals, and to disclose potentialities for interspecies companionship and mutual survival in human-animal borderlands.

[TR] Bu makale, eşikteliği türler arası müşterek bir deneyim ve insan-hayvan bağının kurucu bir unsuru olarak ele almaktadır. Hayvan çalışmaları için barındırdığı potansiyele rağmen, türler arası eşiktelik üzerine yapılmış araştırmalar görece azdır. Bu çalışmanın amacı alanyazındaki bu eksiklikten hareketle Halit Refiğ’in Hanım [Madame] (1989) filmindeki insan ve kedi kahramanların eşiktelik deneyimlerini, temellendirilmiş kuramın kodlama ilkelerini benimseyen incelemesi aracılığıyla araştırmaktır. Filmdeki insan ve kedi baş karakterlerin eşiktelik deneyimleri bu karakterlerin yaşamlarındaki geçişlerle yakından ilişkilidir. Film, Olcay karakteri üzerinden yaşam ve ölüm arasındaki eşiği temsil ederken, Hanım karakteri ile hayvan öznenin kişi-nesne arasındaki belirsiz ve akışkan konumunu ve bununla ilişkili mekânsal aidiyetsizliği resmeder. Araştırma bulguları, eşiktelik yaklaşımının liminal hayvan yerleşimciler gibi hayvan popülasyonlarını tanımlamaya ek olarak, tekil hayvanların yaşamlarını anlamak ve türler arası yoldaşlık ve birlikte hayatta kalma potansiyellerini açığa çıkarmak için kullanılabileceğine işaret etmektedir.
Yaşamın kıyısında türler arası eşiktelik: Hanım’da (1989) insan-hayvan yoldaşlığı